Repressing expression of difficult‐to‐express recombinant proteins during the selection process increases productivity of CHO stable pools - Maltais, Jean‐Sébastien; Lord Dufour, Simon; Morasse, Audrey; Stuible, Matthew; Loignon, Martin; Durocher, Yves (Biotechnology and bioengineering, 2023)
NRC publication: Yes